Definition of an On-Board Comfort Index (Rail) for the Railway Transport - Vincenzo Barone; Domenico Walter Edvige Mongelli; Antonio Tassitani (Journal of Advanced Transportation)
The use of collective transport is strongly influenced by the quality of offered service. One of the overriding factors that affect the modal shift process is the quality of transport systems. To increase the attractiveness of collective transport services and therefore reduce the use of cars, authorities in collaboration with transport companies should take steps to ensure a high level of service quality in the public transport system. The provided quality is the level of quality achieved on daily basis and measured by the customer/user point of view. This research aims to relate service quality perceived by the user to measurements of two environmental indicators, that is, vibration, in reference to which the acceleration transmitted to the body by the vehicle motion and by its vibration will be measured, and noise, in reference to which the Equivalent Sound Pressure Level—Leq (A)—will be measured. Finally, a Comfort Index (CI) (rail) is specified, calibrated, and validated.